2017
DOI: 10.7150/thno.17085
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Sentinel Lymph Node Metastasis by Dual-probe Optical Imaging

Abstract: Purpose: Sentinel lymph node biopsy (SLNB) has emerged as the preferred standard procedure in patients with breast cancer, melanoma and other types of cancer. Herein, we developed a method to intra-operatively map SLNs and differentiate tumor metastases within SLNs at the same time, with the aim to provide more accurate and real-time intraoperative guidance. Experimental Design: Hyaluronic acid (HA), a ligand of lymphatic vessel endothelial hyaluronan receptor (LYVE)-1, is employed as a SLN mapping agent after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Yang et al used HA of different molecular weights (5K/10K/15K) as SLN mapping agents and reported that 10K HA had favourable migration and retention profiles because it binds to Lyve-1 in LNs. The combination of HA and tumour-targeting antibodies (EGFR and HER2) can detect UM-SCC-22B tumour metastasis in SLNs 41 . However, this method of identifying T-MLNs is not ideal because it can only identify partial and fully occupied SLNs due to the minimal blood supply able to deliver the imaging probes to micrometastases and the simultaneous injection of antibody and HA, which should be separated by 24 h. In our study, we found that 5K-HA-HPPS rapidly (<10 min) migrated to pLNs and showed prolonged retention (>12 h) compared with 15K-HA-HPPS.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al used HA of different molecular weights (5K/10K/15K) as SLN mapping agents and reported that 10K HA had favourable migration and retention profiles because it binds to Lyve-1 in LNs. The combination of HA and tumour-targeting antibodies (EGFR and HER2) can detect UM-SCC-22B tumour metastasis in SLNs 41 . However, this method of identifying T-MLNs is not ideal because it can only identify partial and fully occupied SLNs due to the minimal blood supply able to deliver the imaging probes to micrometastases and the simultaneous injection of antibody and HA, which should be separated by 24 h. In our study, we found that 5K-HA-HPPS rapidly (<10 min) migrated to pLNs and showed prolonged retention (>12 h) compared with 15K-HA-HPPS.…”
Section: Discussionmentioning
confidence: 99%
“…The high sensitivity to nodal metastases, real-time imaging of lymphatic drainage patterns, and favorable blood clearance rate of the imaging probes led to a clinical trial of their capability in the specific determination of tumor-bearing lymph nodes [11,12,13]. Animal studies using antibodies were also conducted for the real-time imaging of lymph node metastases [14,15]. The NIR imaging probe cetuximab, an antibody against epidermal growth factor receptor (EGFR), and trastuzumab, an antibody against human epidermal growth factor receptor 2 (HER2), were labeled with a fluorophore (IRDye 800) and studied to determine their ability to detect tumor metastases within SLNs in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…The limited penetration of nanovehicles in tumor or metastases has been evidenced as a major factor limiting their therapeutic efficacy 47 - 49 . The lymph nodes near the original tumor are often the most susceptible sites of metastasis 8 , 50 , 51 . Therefore, the extent of tumor penetration and cellular internalization of r9-CN in primary tumor and metastatic lymph nodes were respectively evaluated.…”
Section: Resultsmentioning
confidence: 99%